2013
DOI: 10.4236/ajac.2013.45028
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Kinetics, Isotherm and Thermodynamic Modeling of Defluoridation of Ground Water Using Natural Adsorbents

Abstract: The aim of study is to investigate the removal ability of some natural adsorbents for fluoride ion from aqueous solution. The batch dynamic adsorption method was carried out at neutral pH as the functions of contact time, adsorbent dose, adsorbate concentration, temperature and effect of co-anions, which are commonly present in water. The sorption kinetics and equilibrium adsorption isotherms of fluoride on natural adsorbing materials had been investigated at aforementioned optimized. Equilibrium adsorption is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…There is growing interest in the application of plant biomass for aqueous F´removal [47][48][49][50][51][52]. The main advantage of plant biomass is that it is readily available and can operate at circumneutral pH.…”
Section: Biomaterial-based Filters For F´removalmentioning
confidence: 99%
“…There is growing interest in the application of plant biomass for aqueous F´removal [47][48][49][50][51][52]. The main advantage of plant biomass is that it is readily available and can operate at circumneutral pH.…”
Section: Biomaterial-based Filters For F´removalmentioning
confidence: 99%
“…Thus, no wonder that a search for effective low cost defluoridation materials is a continuing concern amongst researchers. In recent years, there has been an increasing interest in studying defluoridation characteristics of plant biomasses [9][10][11][12][13][14]. These adsorbents are interesting in that they work optimally at pH between 6 and 7 [9][10][11][12]15] and are sustainably available earth wide.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that with the increase of pH from 7.0 to 10.0 the adsorbent surfaces become more negatively charged and electrostatic attraction from free active groups enhances the adsorption process; however, the reduction in the amount of lead(II) adsorption was observed. In order to explain the reason, the literature attributed this phenomenon to the fact that Pb(OH) 2 is formed at pH more than 7, thus, the optimum pH value for adsorption is where precipitation does not occur significantly (Atieh et al, 2011; Balouch et al, 2013; Faust and Aly, 2013; Molazadeh et al, 2015). The results indicated that the maximum uptake of Pb 2+ was obtained at pH 6 (similar to the results of other researches (Ertaş and Öztürk, 2013; Gupta et al, 2011; Kanjilal et al, 2015)) and Figure 8 also shows that the final pH is 6 for adsorption at condition with initial pH 6, which is indicating that no hydronium uptake has occurred during adsorption.…”
Section: Resultsmentioning
confidence: 99%